Strategi dan Kebijakan Ekspor Impor atau Perdagangan Internasional terhadap Pertumbuhan Ekonomi Indonesia - Ikaningtyas, Maharani; Andarini, Sonja; Maurina, Annisa Cindy; Pangestu, Ilham Asta (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2023)
The level of success in a country can be described by the rate of its economic growth which can be assessed from many aspects such as the value of export activities and import activities which have some influence on the trade balance in a country. Globalization and the era of free trade provide many opportunities for export companies to enter the world market as well as demand the readiness of a company to compete. Theories on international trade are proven to explain several personal business behaviors that are closely related to international trade activities. With good economic growth it will increase national income, people will be more prosperous in terms of the economy. In the last decade, there have been many studies stating that export activities can boost the growth of an economy because they can generate foreign exchange that can be used to finance internal sector development. This problem can arise when the relationship in the economy of a country with other countries both bilaterally and multilaterally so that it can cause several problems that can interfere with the course of international trade so that it can run smoothly, so to overcome some problems it is necessary to find a solution immediately, this is to improve the quality of life of the community. Keywords : export import, international trade, economic growth